PENERAPAN METODE PICTURE AND PICTURE DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SD - Raffid Ciptandri, AA Rega; Al Habib, Muhammad Rifqi; Fitryantika Firrahmawaty, Shalsabylla Alfarezma; Hanzalia, Nadyya Farkha; Prasetiohadi, Rhaffy Hendrika; Indrawati, Delia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early reading ability is a fundamental skill that must be mastered by lower-grade elementary school students as it serves as the foundation for understanding various subjects. However, in practice, students’ early reading skills are often still low due to monotonous teaching methods and the limited use of engaging learning media. This study aims to analyze the implementation of the Picture and Picture method in improving early reading skills of first-grade elementary school students. The study employs a qualitative approach using a literature review method by examining relevant scientific articles from Google Scholar, Garuda, and SINTA. Data collection was conducted through documentation, while data analysis used content analysis to identify patterns and findings from previous studies. The results indicate that the Picture and Picture method is effective in enhancing early reading skills, as evidenced by improvements in learning outcomes, student mastery, as well as increased student engagement and motivation through the use of concrete and attractive visual media. Therefore, this method can serve as an effective alternative learning strategy to improve early literacy in elementary school students, with its effectiveness influenced by the quality of the media and the implementation strategy.